TINJAUAN TEORI KRIMINOLOGI DALAM KEJAHATAN SIBER (KASUS KEBOCORAN DATA NASABAH) : Overview of Criminological Theory in Cyber Crime (Customer Data Leakage Cases) - Gumelar Rizki Duana; Ali Masyar; Cahya Wulandari; duana, Gumelar (Jurnal Hukum PRIORIS, 2023)
Internet or mobile banking is an application or service that connects a device to a banking system. Internet and mobile banking services have many benefits, especially facilitating transactions that only use electronic devices that have internet access. However, with such facilities there are also risks and threats to the users of the tenology services. In some cases, banks may experience digital service disruption caused by hacker attacks. Hacker attacks include cybercrime and violations of the law. Criminological theory can be used to enforce criminal law because it provides answers to the questions of how or why a person and certain behavior are considered evil by society. This study tries to explore criminological theories that can be used in cybercrime in cases of customer data leakage. With the method of juris-empirical research, the author hopes to study the criminological theory in cybercrime, so that the theory can be used to counter its crime in the case of customer data leakage. The conclusion of this study is that there are four criminological theories that can be used to analyze cybercrimes in hacker cases involving customer data leaks, namely: anomie theory, differential association, social control, and neutralization. This criminological theory can be used as a government strategy to take penal and non-penal policy steps against cybercrime in Indonesian banking.